(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to review traditional medicine methods in treating diabetes, identify gaps in previous research, and suggest future research directions. Research methods: A systematic review was used in this study. The search strategy focused on selecting articles from the Vietnam Science and Technology Publication Database (nsti.vista.gov.vn), in the fields of medicine and pharmacy. Full-text articles were collected and screened following PRISMA-ScR guidelines. A total of 25 articles, published from December 2015 to December 2024, were included in the review. Results: Most of the medicinal herbs and traditional remedies studied showed a good effect in lowering blood glucose and did not show acute toxicity when used at relatively high doses in experimental models and some clinical trials. Some typical examples include Gymnema sylvestre, golden flower tea, butterfly pea, dandelion, and herbal combinations such as golden flower tea, Gynostemma pentaphyllum, Celastrus hindsii, Gymnema sylvestre. Conclusion: Traditional medicinal herbs have good potential in the treatment of diabetes. However, to fully evaluate their effectiveness, more clinical studies are needed with large sample sizes and long follow-up periods to confirm their results, long-term safety, and to find the best combination treatment in real clinical practice.